(untitled) (Indian Journal of Chemistry (IJC), 2024)
ABSTRACT Protein tyrosine phosphatase 1B (PTP1B) is an important target for diabetes since inhibition of PTP1B offers therapeutic benefits in insulin resistant diabetes. Unfortunately no drugs are approved or available in market as PTP1B inhibitor and finding of such type of anti-diabetic agents is still in progress. However computational modeling, based on the interaction between co-crystallized ligand and macromolecular receptor presented some structural features required for PTPIB inhibitory activity. Considering these structural features of co-crystallized ligand bound with 3D crystal structure of PTP1B receptor we designed some chalcone and their heterocyclic derivatives as PTP1B inhibitors. Preliminary substituted chalcone were investigated but only one phenyl ring of these derivatives showed interaction with PTP1B receptor in molecular docking study, to overcome this problem some heterocyclic derivatives of chalcone were designed. These heterocyclic derivatives showed interactions similar to co-crystallized ligand means both terminal rings exhibited interactions with macromolecular receptor in molecular docking study. Moreover some of the synthesized heterocyclic derivatives of chalcone showed potent inhibitory activity when tested in-vitro and compound AD-4 ((E)-3-(3-nitrophenyl)-1-(pyridin-4-yl)prop-2-en-1-one) was observed as most prominent inhibitory agent with 75.06 % inhibition of PTP1B. Potent derivative AD-4 also exhibited significant anti-hyperglycemic activity during in-vivo evaluation in animal model